Hubungan Curah Hujan dengan Kasus Demam Berdarah Dengue di Bandar Lampung 2016-2018 - Tusy Triwahyuni; Ismalia Husna; Melisa Andesti (Puslitbang Sinergis Asa Professional, 2020)
Dengue hemorrhagic fever (DHF) is disease caused by dengue virus through mosquito as the vector, which spread rapidly. Meanwhile, since 1968 until 2009 WHO determined Indonesia as a country with the highest DHF incidence in South-east asia Departement of Health of Bandar Lampung City. The study aim to know the correlation of rainfall and dengue incidence in Bandar Lampung City Periode 2016-2018. This analytic study performed correlation approach. Secondary data sources from BMKG and Departement of Health of Bandar Lampung City were obtained. Analyzing data was using SPSS 19. This research was done during January 2020 until February 2020. There were 36 samples from BMKG and department of health of Bandar Lampung city periode 2016-2018 taken using total sampling method. Result show the heaviest rainfall in 2016-2018 recorded in February with average 218,3 mm. The most DHF incidence recorded in March with average 136 incidences. The correlation test shown r= 0,451, N = 36, signification 0,006. There is a correlation between rainfall and DHF incidence with average correlation strength in positive direction.